2020
DOI: 10.3390/s20030729
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Powered and Low Pressure Loss Gas Flowmeter Based on Fluid-Elastic Flutter Driven Triboelectric Nanogenerator

Abstract: A self-powered and low pressure loss gas flowmeter is presently proposed and developed based on a membrane’s flutter driven triboelectric nanogenerator (TENG). Such a flowmeter, herein named “TENG flowmeter”, is made of a circular pipe in which two copper electrodes are symmetrically fixed and a nonconductive, thin membrane is placed in the middle plane of the pipe. When a gas flows through the pipe at a sufficiently high speed, the membrane will continuously oscillate between the two electrodes, generating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…When it flutters in the wind, the alternating contact and separation between the Kapton film and nickel strip can generate electricity, which can be used to harvest wind energy in any direction. However, due to the rigid metal electrode and extreme sensitivity to ambient humidity, the use of most of the demonstrated TENGs in environments with low wind speed and high humidity is limited [ 35 , 36 , 37 ]. Wang et al [ 38 ] reported a humidity-resistant, wind-direction-adapting flag-type TENG capable of collecting wind energy in the environment and serving as a self-powered wind-speed and wind-direction sensor.…”
Section: Introductionmentioning
confidence: 99%
“…When it flutters in the wind, the alternating contact and separation between the Kapton film and nickel strip can generate electricity, which can be used to harvest wind energy in any direction. However, due to the rigid metal electrode and extreme sensitivity to ambient humidity, the use of most of the demonstrated TENGs in environments with low wind speed and high humidity is limited [ 35 , 36 , 37 ]. Wang et al [ 38 ] reported a humidity-resistant, wind-direction-adapting flag-type TENG capable of collecting wind energy in the environment and serving as a self-powered wind-speed and wind-direction sensor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in order to collect different forms of energy more effectively, hybridized nanogenerators are also developed [ 29 ]. Furthermore, because the output voltage and current signals can represent the various dynamic motions triggered by mechanism, the TENGs can also be employed as a variety of self-powered sensors, such as vibration [ 30 ], wind speed [ 31 ], flow rate [ 32 ], displacement [ 33 ], pressure [ 34 ], tilt [ 35 ], and wave [ 36 ] sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, triboelectric nanogenerator (TENG) based on the triboelectrification effect and electrostatic induction has been developed for energy harvesting and self‐powered sensing. [ 13–23 ] The electrostatic charges are generated on the surfaces of two dissimilar materials when they are brought into contact. The contact‐induced triboelectric charges can generate a potential drop when the two materials are separated, which can drive electrons to flow between the two electrodes built on each surface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to explore new gas-solid two-phase flow techniques with robust and high durability performance.In recent years, triboelectric nanogenerator (TENG) based on the triboelectrification effect and electrostatic induction has been developed for energy harvesting and self-powered sensing. [13][14][15][16][17][18][19][20][21][22][23] The electrostatic charges are generated on the surfaces of two dissimilar materials when they are brought intoThe particle concentration and the mass flow rate are the most important parameters describing the gas-solid two-phase flow. Herein, a novel method based on triboelectric nanogenerator is proposed for measuring a particle concentration and the mass flow rate in a gas-solid two-phase pipe flow.…”
mentioning
confidence: 99%